U.S.A. Contemporary Foreign Policy Options & Challenges - الاستاذ الدكتور عبد الغفور كریم علي (College of Education for Women, 2019)
It is out of question that USA foreign policy has a great superiority and influence all over the world. This study deals with all dimensions; aims; and challenges of the American foreign policy. It aims to answer the following question: within the current changes in the world, how can the aims of the American foreign policy be realized?